A Computer-Aided Bibliometrics System for Journal Citation Analysis and Departmental Core Journal Ranking List Generation - Yih-Chearng Shiue; Ray-I Chang; Gen-Ming Guo (Jiàoyù zīliào yǔ túshūguǎn xué, 2004)
Due to the tremendous increase and variation in serial publications, faculties in department of university are finding it difficult to generate and update their departmental core journal list regularly and accurately, and libraries are finding it difficult to maintain their current serial collection for different departments. Therefore, the evaluation of a departmental core journal list is an important task for departmental faculties and librarians. A departmental core journal list not only helps departments understand research performances of faculties and students, but also helps librarians make decisions about which journals to retain and which to cancel. In this study, a Computer-Aided Bibliometrics System was implemented and two methodologies (JCDF and LibJF) were proposed in order to generate a departmental core journal ranking list and make the journal citation analysis. Six departments were taken as examples, with MIS as the major one. One journal citation pattern was found and the ratio of Turning point-to-No. journal was always around 0.07 among the 10 journals and 6 departments. After comparing with four methodologies via overlapping rate and standard deviation distances, the two proposed methodologies were shown to be better than questionnaire and library subscription method.